FORMULATION AND CHARACTERIZATION OF ZEAXANTHIN NANOEMULSION RADIANCE SERUM AS ANTIOXIDANT - SETIAWAN, FAJAR; RUSDIANA, TAOFIK; GOZALI, DOLIH; NURDIANTI, LUSI; IDACAHYATI, KENI; WULANDARI, WINDA TRISNA (International Journal of Applied Pharmaceutics, 2022)
Objective: This study aimed to increase the effectiveness of using zeaxanthin by developed nanoemulsion containing zeaxanthin which was then formulated into radiance serum for topical use. Methods: Nanoemulsions are made using spontaneous nano emulsification methods/techniques, which are relatively simple technologically because they rely on the right combination of selected surfactants and co-surfactants. The optimization of the formula was carried out starting from determining the oil: surfactant: co-surfactant phase ratio and concentration of zeaxanthin. Nanoemulsion characterization in the form of physical characterization includes organoleptic tests, globule size and polydispersity index, zeta potential, pH and entrapment efficiency tests. The best results from nanoemulsion were then combined into serum preparations which were then tested for evaluation of the preparations, including organoleptic, homogeneity, viscosity, pH, spreadability, and antioxidant test. Results: The results showed that the developed zeaxanthin nanoemulsion had a globule size in the range of 20-24 nm (with a normal globule size distribution curve), polydispersity index value of less than 0.3, zeta potential greater than (-20) mV and entrapment efficiency ranging from 80-85%. Conclusion: The results of the evaluation showed that the serum radiance of zeaxanthin nanoemulsion had good physical, chemical and stability properties during storage with an IC50 value of zeaxanthin less than 50 ppm.